2008
DOI: 10.1097/prs.0b013e31818a9a8d
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Video Analysis of the Paralyzed Face Reanimated by Cross-Face Nerve Grafting and Free Gracilis Muscle Transplantation: Quantification of the Functional Outcome

Abstract: Three-dimensional video analysis provided an exact quantitative documentation of the degree of facial palsy preoperatively and the reconstructed movements. The value of free functional gracilis muscle transplantation was demonstrated for both variations of the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
4

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 25 publications
0
49
0
4
Order By: Relevance
“…Although in the most studies [1][2][3]5,6,14,16 on cross-face nerve graft the EEN is the technique used to connect the graft to the donor nerve, some authors [36][37][38] have shown that the ESN (technique more recently introduced 17 ) can also be used successfully. However, to date there is no consensus on the realization of reanimation of the facial paralysis in one or two surgical stages 2,4,9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although in the most studies [1][2][3]5,6,14,16 on cross-face nerve graft the EEN is the technique used to connect the graft to the donor nerve, some authors [36][37][38] have shown that the ESN (technique more recently introduced 17 ) can also be used successfully. However, to date there is no consensus on the realization of reanimation of the facial paralysis in one or two surgical stages 2,4,9 .…”
Section: Discussionmentioning
confidence: 99%
“…However, its disadvantage is that muscle transplant remains denervated for a longer time waiting for axon growth through the nerve graft, which can result in atrophy of muscular fibers, jeopardizing the final result 15 . In the two-stage procedure, the muscle remains denervated for less time, because when it is transplanted, the axons had already grown to the distal end of the graft 2,3,5,6,16 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Draping a free-muscle flap over this convex bony landmark often creates a visible facial deformity. 4 This approach is less than ideal given that the purpose of facial nerve rehabilitation and reanimation is to reduce physical deformity. Many authors have reported successful volume reduction of the harvested gracilis flap as a modification to reduce this problem.…”
mentioning
confidence: 99%